Las sensopercepciones en la inteligencia emocional en la edad infantil” En los niños del inicial I ‘’A’’ de la Unidad Educativa Fiscomisional Purísima de Macas, de la Provincia de Morona Santiago, período 2022 - Rojas Orbe, Jennifer Lisbeth (2022)
The current research called "The sensory perceptions in emotional intelligence in chilldren" at pre-scholar education "A" of the Purísima de Macas Educational Unit in Morona Santiago province period 2022; it was carried out with the objective of analyze the environment where a child develops in his cognitive and emotional domains, being perceptive of the reality that surrounds him, thus influencing his sensory-perceptive development and emotional intelligence. Through this research work, it was proposed to analyze strategies, elaborate a playful guide and didactic material for the development of sensory perceptions and emotional intelligence in children from 3 to 4 years old. Quantitative methods were applied, which allowed us to obtain true data. using the observation sheet as an instrument, we worked with a population of 12 boys and 8 girls, the research design was non-experimental since there was no manipulation of variables, being documentary research, and field since it was carried out in the place of the facts. From the results of this research, we have concluded that it is necessary to apply spaces that allow better sensory-perceptual development, motivating teachers and parents to strengthen self-esteem, autonomy, and empathy in children, which will help in this way. way for children to have a good emotional intelligence and to be able to function better in the environment they find themselves in.